The Influence of WOM, Trust, and Product Quality on Purchase Intention of Maluku Traditional Food Products Moderated by Peers - Limba, Pathrisye Richendi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Word of Mouth (WOM), Trust, and Product Quality on students' purchasing intention on traditional Maluku food products, with Peers as a moderating variable. This study uses a quantitative approach with a survey method, where data is collected through questionnaires and then analyzed using SmartPLS 4. The results show that Word of Mouth (WOM), Trust, and Product Quality have a positive and significant influence on Purchase Intention, which indicates that product quality, level of trust, and positive information or recommendations play a significant role in increasing students' purchasing intention on traditional Maluku food products. Peers do not directly influence purchase intention. However, in its role as a moderating variable, peers are proven to influence purchase intention. The influence of Word of Mouth on Purchase Intention is moderated, while it is unable to moderate the relationship between Product Quality and Trust on students' Purchase Intention. These findings indicate that students' purchasing intention is more influenced by internal consumer factors and product characteristics, while social influence plays a limited and contextual role. This study is expected to be a consideration in developing marketing strategies for traditional Maluku food products in the future and as a reference for further research.